Холостая война: [роман] / Сергей Зверев - Зверев Сергей Иванович (Спецназ, 2014)
Экземпляры: Ф. 12 (20190722) / Инвентарный номер: 46472 / Цена: 70.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6